The federal principle as a constitutional framework for resolving the national issue - Iraq's federal constitution as a model - Karim, Mohamed Saber (Journal of Legal and Political Studies, 2021)
The federal system, as if one of the most principle and framework powerful to dividing the authority in the societies in which had covered with multiethnic and multicultural, or which had have the widely geographic area,is consider as one succeed solution to the problems of the distribute of the power. Thus this constitutional formula of the relation between the stats and its regions beginning through progress and developing as one of the main phenomenon of the political live in the modern and contemporary stats to be held by those political systems in which taken with management and regional measure basic of dividing of the powers in it. Thus those positive signification of the federalism have stand behind the new political system the Iraqi state as a main factor after the fall dawn the previous regime in the 2003,in order to be held this type of democratic systems in it the new constitution, taken it as a aim to relevant solution to the Kurdish issue in it, as if the one of the difficult issue which is this stat facing with it since it had been established at the bigine of second decade of the twenty century, through the organizing the constitution relation between the Kurdistan region and the centralize authority in Baghdad as the basic of it.
Keywords: Federalism; Constitution; Federal system; Iraq; Kurdistan Region